Effectiveness of Find Someone Who Method in Improving English Speaking Skills in Lombok Tourism Polytechnic Students - Kufrabawa, Wendi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to analyze the effectiveness of the